Theoretical model of caustics method for the interfacial cracks. (15th June 2020) - Yuan, Yanan; Zhang, Qiang; Sheng, Can; Zhang, Zuoqi
Highlights: A unified theoretical model of caustics method for the interfacial cracks has been induced which was applicable for all material systems including dissimilar isotropic and orthotropic materials, isotropic-orthotropic bi-materials, and homogeneous isotropic and orthotropic materials. The transmission optical method of caustics combination with high-speed camera under impact load in the bi-material system were conducted and it is an effective experimental method to measure the dynamic stress intensity factors in the interfacial crack tip. The influence of mixed crack mode, elastic modulus mismatch, crack velocity and fiber orientation on the shape of initial and caustic curves have been studied which also directly affect the dynamic stress intensity factors. Abstract: As a non-contact optical experimental method, caustic method is commonly employed in measuring stress intensity factor at the crack tips of different materials. Caustics theory is commonly used for solving stress intensity factor at crack tips in homogeneous isotropic materials, but it lacks the required accuracy for solving stress intensity factor in interfacial cracks in dissimilar materials. In this paper, we have deduced the theoretical equation of stress intensity factor at interfacial crack tips the orthotropic bi-materials and evaluated the effects of different crack propagation speeds, orthotropic bi-materials and other parameters on the initial curves of focal line and the shape of caustics. In addition, dynamic caustic experiments on composite/epoxy bi-materials under low velocity-impact loadings were performed and the evolution of dynamic interfacial cracks was captured by high-speed cameras which showed good agreements with theoretical results. Research results confirmed the usefulness of the application of caustic method in dissimilar isotropic and orthotropic materials, isotropic-orthotropic bi-materials and homogeneous isotropic and orthotropic materials under subsonic crack propagation velocities.